A new theory of tree sap flow - Török,András; Hajduné Kubovje,Anikó Anna; Hardi,Balázs; Bergmann,Ralf; Szigeti,Krisztián; Máthé,Domokos; Hegedüs,Imre (PeerJ, 2025)
Introduction The theory of water transport in trees, according to which the main driving force of water movement is the suction created by the evaporation of water by the meniscus (the curved surface of the capillary liquid column) on the evaporating elements, supported from below by root pressure, is controversial. The main physics argument against it is that the capillary effect in nature is around 1 m. In the case of open-air gaps, the leaf cannot suck in the water against gravity because, in this case, the plant would not be sucking in water, but air through the open-air gap. Aim To present a new theory of three-sap flow and to support it with practical observations, previous data from decades of experimental measurements, and direct measurement data obtained by the authors. New theory When evaporation occurs, there is no suction towards the canopy, but pressure is due to a reduction in the cross-section of the water pipe caused by heat loss through evaporation. At night, when evaporation stops, a thermal equilibration process is triggered, restoring the pipe’s original cross-section. This generates suction and draws water from the soil. As the hydrostatic pressure in the pipe is high for tall trees, the pipe is segmented. Materials and Methods To study the change in the wood’s cross-section, a mechanical pressure-sensing transmitter-amplifier instrument was used. The instrument is designed to convert changes in the diameter of a millimeter-sized tree into easily detectable data by increasing the diameter by an order of magnitude. We also used high-resolution computer tomography (CT) to measure the cross-sectional image of oak trees to explore areas rich in water. Results The experimental results show that the tree diameter increases during the night (suction phase) and decreases during the day (pressure phase). Many measurements in the literature show a similar phenomenon. The CT scan results showed that the outer, living one-ring area of the tree is rich in water, from which passages lead to the passive water storage inside the tree. Conclusions Several examples have been given to prove this theory. Water transport is not based on physical mechanical laws alone. Complex physiological, biochemical, and biophysical processes may be behind the operation of the pipe system.
Keywords: Water transport in trees; Suction-pressure pipe; Pulsating system; Different time-phase cycle; Aquaporin